Matrix Multiplication using Strassen’s Algorithm on CPU & GPU - Ray, Utsab; Hazra, Tapan Kumar; Ray, Utpal Kumar (International Journal of Computer Sciences and Engineering, 2025)
In this paper we have successfully implemented Matrix Multiplication using Strassen's Algorithm on a NVIDIA GPU using CUDA. We have used the multiple cores of the GPU to reduce the computation time drastically. We have also compared the time taken by matrix multiplication using Strassen's algorithm on both CPU and GPU. We have found that the GPU implementation was much faster, but only when the recursion was performed till a certain limit. Beyond that limit, the computation took much more time than expected. Also, we found that implementing Matrix Multiplication using Strassen's algorithm on the CPU yielded some very positive results. By conducting experiments, we came to the conclusion that the recursion limit can be comparatively smaller for matrix multiplication using Strassen's algorithm on CPU than for matrix multiplication using Strassen's algorithm on GPU.